국내 닭의장풀에서 분리된 오이모자이크바이러스 분리주들의 외피단백질 유전자와 병징 다양성 비교 - 박태선(Tae-Seon Park); 홍진성(Jin-Sung Hong) (Sigmulbyeong yeon'gu, 2018)
Three isolates of Cucumber mosaic virus isolated from Commelina communis plants showing chlorosis and mosaic were collected in Chungju and Chuncheon, Korea. To confirm genetic variation of these three isolates (CMV-Co, CMV-Co2, and CMV-Co3), we performed PCR-RFLP and sequence analysis. Sequences of coat protein genes of CMV-C0, -Co2 and -Co3 were compared with CMV-Fny and showed 96.3%, 96.3%, and 95.9% similarities, respectively. In host reactions, three CMV-Co isolates induced systemic necrosis in Cucurbita pepo unlike CMV-Fny and CMV-Co, CMV-Co2 and CMV-Co3 observed differential symptoms responses in Physalis angulata and Nicotiana rustica. These results indicated that three isolates of CMV isolated from C. communis have genetic and biological variation. 춘천과 충주에서 퇴록현상과 모자이크 병징이 뚜렷한 닭의 장풀을 채집하여 바이러스 분리 동정하였다. 해당 바이러스는 RT-PCR과 RFLP 분석결과 CMV로 동정되었으며, 닭의장풀 CMV 분리주들은 서로 다른 서브그룹으로 존재하고 있는 것이 확인되었다. 외피단백질유전자의 염기서열을 분석한 결과, 각 CMV 분리주들은 CMV-Fny와 비교 하였을 때 CMV-Co와 96.3%, CMV-Co2는 96.3%, CMV-Co3는 95.9%의 유사성을 나타내었다. 또한 기주 반응 분석 결과 닭의장풀 분리주들은 대조바이러스(CMV-Fny)와 달리 C. pepo에서 전신 괴사병징이 특징적으로 나타났으며 Physalis angulata과 N.rustica의 경우 닭의장풀 분리주 간에 병징의 차이를 보였다. 이들 결과를 통해, 국내 닭의장풀에서 분리된 CMV들에서 유전적, 생물학적 다양성이 있는 것으로 확인되었다.